Two-category place representations persist over body rotations. - Pyoun, Hyoun; Sargent, Jesse; Dopkins, Stephen; Philbeck, John (Memory & Cognition, 2013)
We explored a system that constructs environment-centered frames of reference and coordinates memory for the azimuth of an object in an enclosed space. For one group, we provided two environmental cues (doors): one in the front, and one in the rear. For a second group, we provided two object cues: a front and a rear cue . For a third group, we provided no external cues; we assumed that for this group, their reference frames would be determined by the orthogonal geometry of the floor-and-wall junction that divides a space in half or into multiple territories along the horizontal continuum. Using Huttenlocher, Hedges, and Duncan's ( Psychological Review 98: 352-376, ) category-adjustment model (cue-based fuzzy boundary version) to fit the data, we observed different reference frames than have been seen in prior studies involving two-dimensional domains. The geometry of the environment affected all three conditions and biased the remembered object locations within a two-category (left vs. right) environmental frame. The influence of the environmental geometry remained observable even after the participants' heading within the environment changed due to a body rotation, attenuating the effect of the front but not of the rear cue. The door and object cues both appeared to define boundaries of spatial categories when they were used for reorientation. This supports the idea that both types of cues can assist in environment-centered memory formation.